The Twisted Nose: What to Do When It's Not Straight - Gonzalez, Joseph R.; Winkler, Andrew A. (Facial Plastic Surgery, 2018)
Septorhinoplasty is among the most common facial plastic and reconstructive surgeries and its complexities are reflected in a relatively high revision rate. The patient with a postoperative twisted nose presents an additional challenge and requires that the surgeon display empathy and possess a deep knowledge of the aesthetic and functional intricacies of the nose. Correction of the twisted nose should be approached in a systematic fashion with unique considerations for each “third” of the nose. While there are many options in the overall surgical armamentarium, each surgeon will find specific techniques that are most efficacious and reproducible for their individual practice. This article discusses select surgical “pearls” and techniques that can aid the surgeon in their own surgical decision-making.
Keywords: revision rhinoplasty; acquired nasal deformity; osteotomy; caudal septal deviation; twisted nose